Kemampuan Koneksi Matematis Mahasiswa dalam Pemecahan Masalah pada Perkulihan Kalkulus Intergral di IAIN Batusangkar - Christina Khaidir; Vivi Ramdhani (Journal on Education, 2023)
The purpose of this study is to describe the ability to connect students' mathematical concepts in problem solving, to describe students' mathematical connection skills to other disciplines in problem solving, to describe students' mathematical connection skills to everyday life in problem solving in Integral Calculus lectures at IAIN Batusangkar. This type of research is mixed methods research, which is a research step by combining two forms of approaches in research, namely quantitative and qualitative. The approach that the author uses in this research is a quantitative and qualitative approach in a commensurate level to understand a phenomenon that is being studied. The qualitative approach aims to analyze and describe students' mathematical connection abilities in problem solving. While the quantitative approach is to see the category of students' mathematical connection abilities in problem solving. The instrument used is a test of learning outcomes and interview results. This test aims to determine the subject's connection ability in solving problems that have been given in learning. After doing the test and the results were analyzed by the researcher, the next step was for the subject to be interviewed related to the subject's ability to do the mathematical connection test. Furthermore, the test results are compared with the results of the interviews. The results showed: the ability to connect mathematics with other sciences (science fields) and the ability to connect mathematics with everyday life were included in the very good category. While the ability to connect between topics / concepts in mathematics is included in the medium category